Prawo do bycia zapomnianym w internecie – za życia i po śmierci? - Dubis, Wojciech; Daćków, Marta (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The commercial development and the transfer of data between the states and the commercial entities which is related with this development significantly influenced the importance of internet, both in the commercial trade and with regard to the services rendered to consumers. The wide extent of the exchange of data, as well as the efficiencies and the dangers connected with this, causes that the modern legal systems are facing new tasks. Undoubtedly, one of the essential of them is to determine the norms and frontiers related with the protection, processing, collecting and sharing of the personal data. Given the fact that the personal data placed on the internet are not subject to any temporal or territorial control and the fact that there exist doubts connected with the influence of the internet search engine on the shaping of the access to the information, the analysis of the previous legal standards of the protection of personal data became necessary
Keywords: right to be forgotten; cult of the deceased; protection of personal data in the Internet; Internet